253 Innovative Teaching Early in Medical Career to Expose Medical Students to Surgery. (28th February 2022) - Hennessy, M.; Johnson, J.; Spence, T.; Justusson, D.; Paladugu, M.; Shetty, V.
Abstract: Aim: At Lancashire Teaching Hospitals medical students begin their clinical career in Year 3 and are posted in General Surgery for 4 weeks, a relatively short period to experience the wide variety of surgical specialities and operative techniques. A surgical skills course - Lancashire Teaching Hospitals Surgical Skills for Medical Students (LTHSSMS) was designed and piloted. The aim was to assess the student experience of the LTHSSMS course conducted for Year 3 students at Lancashire Teaching Hospitals in 2019. Method: This all-day course was optional, taught in groups of 15 students per course with a minimum of 2 experienced tutors. The LTHSSMS course included practical skills such as scrubbing, gloving, surgical knotting, suturing, excision of skin lesions and local anaesthetic techniques. It also included lectures on suture materials, abdominal incisions, laparoscopic and robotic surgery. There were interactive discussions to include non-technical skills, theatre in brief and WHO checklist. Results: 95% (n- 86) of students posted in surgery attended the course. 86.3% (n-75) felt the course was very relevant for their training. 90.7% (n-78) stated they enjoyed the course and 98.8% (n-85) stated they would recommend the course to fellow third-year students. 97.7% (n-84) stated the tutors delivered the course in an enthusiastic and positive manner. 79.1% (n-68) rated the audio video as excellent. Conclusions: This course has provided a high impact surgical experience for the medical students at the beginning of their clinical careers. Similar opportunities if made available to students in all medical schools could improve and renew the interest in a surgical career.